FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN NON- KEUANGAN DI INDONESIA - Margaretha; Dewi Sari Wijoyo (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to obtain empirical evidence about whether managerial ownership, institutional ownership, capital structure, profitability, company growth, company size, liquidity, investment policy and activities influence the firm value. The data of this study consisted of 100 non-financial companies with 3 years of data, 300 data. The samples were selected using the purposive sampling method. And the method of data analysis in this study uses hypotheses with multiple linear regression. The results of this study indicate managerial ownership, capital structure, profitability, liquidity and investment policies significantly influence the firm value. While the other four independent variables, namely institutional policy, company growth, company size and activity do not significantly influence the firm value